Developing a nano-Fe Complex to Supply Iron and Improve Salinity Tolerance of Pistachio under Calcium Bicarbonate Stress. Issue 14 (5th August 2020) - Karimi, Soheil; Tavallali, Vahid; Ferguson, Louise; Mirzaei, Shima
ABSTRACT: Iron (Fe) is chronically low in saline sodic soils. The effect of nano iron (Fe) particles complexed with salicylic acid (nFe-SA) on the Fe supply and salinity tolerance of Pistacia vera 'Akbari' seedlings were compared with seedlings grown in a control Hoagland nutrient solution amended with Fe-EDDHA. The saline treatments were prepared by adding 0 (control), 100, and 200 mM NaCl to the nutrient solutions. Moreover, calcium bicarbonate (0.2% w/v) was added to all these treatments. Plant growth, water relations, injury indexes, and mineral composition were investigated after 75 days. Growth and chlorophyll content of the plants was the same with both nFe-SA and Fe-EDDHA treatments under non-saline conditions. Increasing salinity stress restricted plant growth, and reduced leaf relative water content and water potential. Leaf abscission due to Na accumulation was the major cause of biomass loss and plant growth inhibition. Salinity also reduced leaf inorganic nutrient concentrations and produced leaf oxidative damage. However, under salinity stress, the nFe-SA treated plants had less leaf abscission and growth limitation than the Fe-EDDHA plants. The nFe-SA application decreased plasma membrane damage and chlorophyll degradation. Salinity stress increased Zn, Cu, and Fe concentrations in the Fe-EDDHA treated plants. However, low chlorophyll concentration in these plants indicated that inorganic nutrients were not functional. The results suggest nFe-SA can be an effective and environmentally friendly Fe source in saline and calcareous alkaline soils.